The Development of the Imigrant Community From Java in Batu Pahat, 1957-1966 - Ovi Fauzia Tihamayati; Sahul Hamid bin Mohamed Maiddin; Ahmad Zainudin bin Husin (Green Publisher Indonesia, 2022)
This study aims to look at the history of the development of Javanese society in Batu Pahat from 1957 to 1966. In this study, the author tries to explain the influence of relations between Malaysia and Indonesia from 1957 to 1966 on development and culture immigrants from Java who moved to the Batu Pahat area. This research uses the historical method with an interdisciplinary approach that uses the help of other social sciences such as Sociology and Anthropology. Data collection techniques using literature review techniques, publications, and documentation studies. The results of this study explain that the ups and downs of the relationship between Malaysia and Indonesia in that year gave an impression on the development of the Javanese community in Batu Pahat. For example, from 1957 to 1962 the relationship between the two countries were close and friendly, and made the Javanese community in Batu Pahat begin to join into the various fields and play an important role in fostering development in Batu Pahat. But in 1963 to 1966, relations between Malaysia and Indonesia began to get worse. This is because Indonesia confronted Malaysia. Apart from that, at this time, the Javanese people in Batu Pahat were experiencing difficulties in various fields.